The challenges of tax policy: a literature study on market and welfare dynamics - Tingkes, I Nyoman; Sirna, I Ketut; Sumartana, I Made; Widnyani, Ida Ayu Putu Sri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Taxes are the government's primary tool for collecting revenue, but their implementation presents challenges such as deadweight loss, market shrinkage, and impacts on welfare and economic efficiency. Appropriate tax policy is needed to optimize state revenue while maintaining market balance and public welfare. The purpose of this study is to deeply analyze how tax policy affects market dynamics and economic welfare, both on the producer, consumer, and government sides. This research uses a qualitative literature review approach to analyze the impact of tax policy on market dynamics and economic welfare. Data was gathered through documentation from academic sources such as Google Scholar, PubMed, and ScienceDirect, focusing on publications from the last five years. The data was analyzed in three stages: reduction, presentation, and conclusion drawing, to provide a comprehensive, evidence-based understanding and policy recommendations. The study finds that tax policy implementation often results in deadweight loss, reflected in the decrease in total surplus for both producers and consumers. Taxes on elastic goods and services tend to severely impact welfare, highlighting the need for more careful policy design. High tax rates can shrink the market size, ultimately reducing government revenue. Policymakers must balance elasticity levels between producers, consumers, and tax rates to optimize both economic welfare and state revenue. To improve effectiveness, concrete policies are needed, such as progressive tax rates, regular monitoring of tax impacts, and incentives for certain sectors.